Cycling and spinal trauma: A worrying trend in referrals to a national spine centre. Issue 4 (August 2018) - Broe, M.P.; Kelly, J.C.; Groarke, P.J.; Synnott, K.; Morris, S.
Abstract: Introduction: Cycling has seen a large increase in popularity worldwide over the last number of years. This has been linked to an increase in the number of road traffic accidents involving cyclists. Participation in cycling as part of competitive sport and endurance events has seen particular growth. Aim: To examine patients referred with spinal trauma related to cycling and to assess whether the growing popularity of cycling and particularly competitive cycling is linked to an increase in spinal trauma. Methods: A retrospective analysis was carried out of a prospectively maintained database of referrals to a national referral centre for spinal trauma over a 4-year period (2010–2013). Data were further analysed for years 2012–2013, as there were incomplete data for years 2010–2011. Results: Spinal injuries involving cyclists increased by 200% from 2010 to 2013. In comparison those involving cars only increased by 29% and motorcycles reduced by 68%. From 2012 to 2013 there were 24 cyclist trauma referrals. The most common level injured was cervical spine (71%). Five patients (20.8%) had neurological deficit with 12.5% complete paralysis ASIA A disability score. The spinal fixation rate was 29.1%, 16.6% were managed with a HALO device. In total, 25% of patients were injured whilst training on a racer style bicycle, including all of the patients with complete spinal cord injury. Conclusion: There has been a significant increase in spinal trauma due to cycling accidents over this four year period. Competitive cycling has been a factor in the most severely injured patients. Increased public awareness campaigns for those participating in cycling for sport may be warranted.